Morphological studies on the cupulae of free neuromasts along with the growth of larvae in cyprinid fish - Mukai, Yukinori; Kobayashi, Hiroshi (Japanese Society of Fisheries Science, 1991)
The free neuromasts were morphologically investigated in the larvae of two cyprinid fish, Zacco platypus and Gnathopogon elongatus caerulescens. In Z. platypus that mainly inhabits rivers, cupulae increased in length and became flat in shape (the so-called nail type) along with growth in the larval stage. Afterwards, the cupulae became shorter during the juvenile stage. The short and nail type cupulae of Z. platypus seem to be adaptive to rheotactic swimming. On the other hand, in G. elongatus caerulescens that lives in lakes, the cupulae were long and did not change in length until the 72nd day after hatching in the juvenile stage, but it changed in shape from a stick to a flat type like marine algae (laminaria). The surface area of these cupulae is larger than that of Z. platypus, and therefore the cupulae of G. elongatus caerulescens will be more receptive to mechanical stimulus by water flow. The photographs (SEM) of neuromast showed that the direction of the best physiological sensitivity of sensory hair cells coincided with the minor axis of the outline of the neuromast area, namely the bending direction of cupulae. From these results, it was considered that the neuro-masts of G. elongates caerulescens have a high sensitivity not only regarding their swimming behavior but also for perceiving weak water movements caused by prey and predators.